The literary process in Kazakhstan: modern interpretationsание (Eurasian Journal of Philology Science and Education, 2016)
The author explores the main trends of the development of modern literary process in Kazakhstan and overviews the research, reflecting the artistic features of the modern epic genres: novel, story, story. The works published in the period of Independence are analyzed in the article.The author researches the philosophical horizons, genre transformation, the archetypal characters of modern Kazakh literature. This article examines how the ethnic identity and national world are reflected in the works of Kazakh writers. The author reviews modern literary criticism and defines the features of theme, genre «tribal thinking», typology, context of historical prose. The author reveals the phenomenon of the popularity of the historical novel, reflecting the metaphysics of the national spirit revising outdated concepts of the national history, artificially tearing literature away from the national existence.
Keywords: literary process; literary criticism; novel; story; genre transformation; typology